One new species and one new record for the genus Mesogastrura (Collembola, Hypogastruridae) from Korean caves, with DNA barcodes - Chang, Gyu-Dong; Kim, Sun-Sook; Park, Kyung-Hwa (Zootaxa, 2022)
We collected one new species and one new record in the genus Mesogastrura Bonet, 1930 (family Hypogastruridae) from three caves with different origins in the Korean Peninsula; Mesogastrura seotalensis sp. nov. and Mesogastrura ojcoviensis (Stach, 1919). The genus Mesogastrura Bonet, 1930 is newly recorded from the Korean Peninsula. Mesogastrura seotalensis sp. nov. shows various body color (light brown or much less and light purple), 3 + 3 eyes and unguis with three inner teeth. On the other hand, Mesogastrura ojcoviensis (Stach, 1919) is characterized by white body color, 2 + 2 eyes and unguis without inner tooth (rarely with 1). These species were found in piles of bat’s guano inside of caves, so they are considered as troglophilous and guanophilous species. Partial DNA sequences of mitochondrial cytochrome c oxidase subunit I (COI) gene were used as DNA barcodes to clarify the species delimitation.